Artistic-figurative features of cosplay heroes in the context of reaching a tourist attraction - Артеменко, М. П.; Агаджанян, І. С. (Art and Design, 2018)
The study seeks to systematize artistic-figurative features of cosplay heroes in the context of achieving tourist attraction taking into account the cultural traditions of the eastern (Japanese) and western (American-European) directions of this subculture. The research includes a critical analysis of publications on selected topics, analytical processing and systematization of the collected information base of the study with photo-illustrative material, in which examples of costumes for cosplay are recorded. Also, the visual-graphic methods of data processing were used in the work, which allowed to illustrate clearly the characteristic conceptual directions of artistic images of the eastern and western directions of this subculture. Four groups of artistic images of cosplay heroes of the origin are distinguished, as well as fundamental differences in the images of the eastern and western directions of cosplay are revealed. For the Western (American-European), a classification scheme consisting of 12 basic groups of characters with distinctive external features was formed; for the eastern (Japanese), a more complex hierarchical structure that contains three global categories (images of the "real world", "fictional world", "the medieval world") and one auxiliary (fanservice images). Global categories of images are divided into 9 groups. For the first time, scientific analysis and systematization of artistic-figurative features of heroes of cosplay have been conducted taking into account the specifics of the cultural traditions of the eastern (Japanese) and western American-European) directions of this subculture. The results of the research can be used in pedagogical activities in teaching a number of disciplines related to the design of a spectacle and theatrical costume, as well as in the practice of designers, costume designers, cosplayers, tourism managers, etc.